KARAKTERISASI ENZIM PROTEASE DARI BAKTERI Stenotrophomonas sp. ASAL GUNUNG BROMO, JAWA TIMUR - Yati Sodaryati Soeka; Sulistiani Sulistiani (Research Center for Biology-Indonesian Institute of Sciences, 2017)
Protease is an enzyme that can hydrolyze protein into simpler compounds, i.e peptides and amino acids. Microbial Proteases have the potency to be applied in industries such as detergents, skins, silver recovery, dairy, baking, beverages and pharmaceutical industries. These hydrolytic enzyme are efficiently involved in the food industry to increase the nutritional value, digestibility, palatability, flavour and reducing allergenic compounds as well as in the management of domestic and industrial wastes. The purpose of this study was to investigate the ability of Stenotrophomonas sp. isolated from Mount Bromo, East Java in producing protease. Protease activity of the bacterial isolate was qualitatively determined by formation of a clear zone surrounded their colonies on media containing skim milk (1%). We analyzed its proteolic activity against some effects of the incubation period, pH, temperatures and addition of monovalent and divalent metal ionsquantitatively using a spectrophotometer at ? 280 nm.The results showed that the optimum activity after incubation for two days was 315.88 U/ mL. The enzyme has continued to its activity at pH 8 (419.68 U/mL) and maintained its stability at 398.22 U/mL with activities decreased to 94.87%, while its activity at 60°C was 519.86 U/mL and could maintain its stability at 419.58 U/ mL, the activity decreased to 74.75%. The addition of Ca2+ could activated its enzyme activity at the amount of 424.33U/mL, while without addition of the ion its activity was 400.29 U/mL. The addition with ion Mn²+, K+, Na+ and Cu 2+ could act as inhibitors that might reduced the activity of the enzyme.